2001
DOI: 10.1038/35107085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory PAS domain protein is a negative regulator of hypoxia-inducible gene expression

Abstract: Alteration of gene expression is a crucial component of adaptive responses to hypoxia. These responses are mediated by hypoxia-inducible transcription factors (HIFs). Here we describe an inhibitory PAS (Per/Arnt/Sim) domain protein, IPAS, which is a basic helix-loop-helix (bHLH)/PAS protein structurally related to HIFs. IPAS contains no endogenous transactivation function but demonstrates dominant negative regulation of HIF-mediated control of gene expression. Ectopic expression of IPAS in hepatoma cells selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
464
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(490 citation statements)
references
References 22 publications
(16 reference statements)
8
464
0
9
Order By: Relevance
“…The trans-regulation between HIF-3α and HIF-1α was suggested by Makino et al [41], who demonstrated that an alternatively spliced variant of mHIF-3α was a dominantnegative regulator of mouse HIF-1α. Recently, Marynard et al [33] found hIPAS, which they named hHIF-3α2.…”
Section: Discussionmentioning
confidence: 93%
“…The trans-regulation between HIF-3α and HIF-1α was suggested by Makino et al [41], who demonstrated that an alternatively spliced variant of mHIF-3α was a dominantnegative regulator of mouse HIF-1α. Recently, Marynard et al [33] found hIPAS, which they named hHIF-3α2.…”
Section: Discussionmentioning
confidence: 93%
“…HIF-1α is ubiquitously expressed, whereas HIF-2α (also called EPAS (endothelial PAS protein), HLF (HIF-1α-like factor), and HRF (HIF-related factor)) and HIF-3α exhibit more restricted tissue distributions. HIF-2α is expressed primarily in the vasculature of the early developing embryo and subsequently in the lung, kidney interstitial cells, liver parenchyma, and neural crest cells 116-118HIF-3α mRNA and protein are primarily detected in the thymus, kidney, cerebellar Purkinje cells, and corneal epithelium of the eye 119,120 . HIF-1β/ARNT is constitutively expressed and is largely insensitive to changes in O 2 levels, whereas all three HIF-α subunits are acutely regulated by hypoxia (see Box 2).…”
Section: Box 1 Hypoxia-inducible Factors: Subunit Complexitymentioning
confidence: 99%
“…IPAS is an alternative splicing product of the HIF-3 locus that lacks the C-terminal transactivation domains of the HIF-1 and -2 [39]. As such, it competes with HIF-1 for binding the  subunits acting as a dominant negative regulator of HIFs [40]. The IPAS-specific splicing product of the HIF-3 locus is hypoxia-inducible and 8 HIF-1 binds to the hypoxia-responsive cis-element of the IPAS promoter representing a classic negative feedback that restricts HIF-mediated gene expression in hypoxia (Figure 2A) [39,41].…”
Section: Transcriptional Feedbackmentioning
confidence: 99%